A Dança na Escola: um sério problema a ser resolvido - Pires de Sousa, Nilza Coqueiro [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP]; Caramaschi, Sandro [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
Pretendemos abordar os aspectos relacionados à Dança na Escola e pensarmos sobre uma formação continuada, a fim de discutir e refletir a elaboração de propostas de capacitação em Dança voltadas aos professores de Educação Física, principalmente no interior do Estado de São Paulo. Analisaremos a formação inicial dos professores, objetivos, conteúdos e possibilidades de aplicação da Dança no contexto educacional. Apesar do aumento das pesquisas em relação ao ensino da Dança na Escola, falta um espaço adequado e professores comprometidos com um trabalho sério, consciente e crítico, pois a hegemonia do esporte se encontra muito arraigada na cultura escolar. Uma forma de amenizar esse problema seriam cursos de capacitação, de forma permanente, voltados aos conteúdos de Dança, a fim de que esses professores possam ter vivências em práticas dançantes embasadas em uma fundamentação teórica para, assim, discutir, analisar e refletir a melhor maneira de trabalhar esta arte no âmbito escolar.

This work aims to approach the aspects related to Dance at School and reflect about a possible way of continuing education, so we can promote a discussion and reflection in order to elaborate proposals of training in Dance for Physical Education teachers, mainly in the interior part of São Paulo State. In the literature review, we analyzed the initial teachers' education, objectives, contents, and possibilities of applying the Dance inside the educational context. Through bibliographical analysis, despite the increase of researches related to teaching Dance in School, we noticed that it needs a long way to go, in order to find appropriate space and also find teachers who are committed to serious, conscious and critical work because the sport hegemony is deeply rooted in the school culture. We concluded that one of the ways to ease this problem would be through training courses (in a permanent way) which are focused in dancing contents and, as a result, the Physical Education teachers can experience practical dancing experiences based on a theoretical basis. This way, teachers can discuss, analyze and reflect about the best way to approach Dance inside school.
The Dance inside School: a serious problem to be solved
Keywords: Dance; Training; School; Continuing education